Pengenalan Sejarah Kuliner Khas Palembang (Martabak Har) Kepada Siswa SMA Muhammadiyah 3 Palembang - Apriana Apriana; Yuliarni Yuliarni; Nur Ramadhan; Wendy Anugrah; Fatmah Fatmah; Nurhayati Nurhayati (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2026)
The development of globalization and popular culture has influenced young people’s habits, particularly in consumption patterns and lifestyles, which has led to a declining interest in local history and culture. One form of local culture that is closely connected to the daily lives of the younger generation is traditional cuisine. This Community Service Program (Pengabdian kepada Masyarakat/PkM) aims to strengthen the understanding of South Sumatra’s local history through the introduction of Palembang’s traditional culinary history, namely Martabak HAR, by adapting the approach to the habits and interests of young people. The program targeted students of SMA Muhammadiyah 3 Palembang as representatives of the younger generation. The activities were conducted through interactive lectures, participatory discussions, the use of visual and digital media, and by linking the history of Martabak HAR with contemporary youth culinary consumption habits and social activities. The results indicate an improvement in students’ understanding of local history as well as the growth of awareness regarding the importance of preserving traditional cuisine amid the dominance of modern food culture. Moreover, students showed positive responses as the materials were delivered in a contextual manner and were relevant to their daily experiences. This PkM activity demonstrates that a youth habit–based approach through culinary history can serve as an effective strategy for strengthening local history and shaping the cultural identity of the younger generation.